STRATEGI MENGAJAR GURU DALAM MENINGKATKAN MINAT BELAJAR SISWA - Willem Hetharion (IAKN Ambon, 2018)
In the process of teaching and learning teachers have the task to prepare lesson plans and in it there are strategies that must also be prepared. Strategy is a way that teachers should pay attention and apply well in teaching and learning process, so that will impact on teaching and learning atmosphere and involvement of students in following the learning process. The problem is the character of the child who is difficult to manage or the child who tends to want to play rather than follow the teaching and learning process, it will result in the learning process becomes hampered, and will disrupt the attention and involvement of other students in the learning process. According to the results of this writing that with a strategy that has been well prepared by teachers, in the process of teaching and learning will make the course of teaching and learning process to be effective, and fun. But when the teacher does not prepare the strategy well in the delivery process of the material, will be not maximized, the child will feel bored and the child will prefer to play than to receive the teaching that the teacher gives, so strategy is a thing that can generate interest, which can create a sense of fun, to follow the learning process. Strategy includes all the things teachers do in the learning process. The results can be seen from the students' ability when doing the task given by the teacher. From the results of this study it can be concluded that the strategy of teaching a good teacher and creative with attention to the character and style of student learning, can make students attention and involved in the learning process.